Challenges to research universities - Noll, Roger G. (Washington, D.C. : Brookings Institution Press, 1998)
In the 1990s, research universities have experienced the first protracted challenge to the boom of the preceding four decades. This book examines the nature of the challenges to research universities and their likely effects on the number, size, and operation of these universities.
The authors assess the prospects for research support from government, industry, and profits from university medical centers and conclude that the future does not appear bright in these cases. They also examine the methods used by the federal government to pay for university research, and they propose changes that would make both universities and the federal government better off by reducing the administrative costs of federal grants. Their primary conclusion is that in the next decade American research universities will face increasingly stringent budgets, forcing them to shrink and refocus their activities in order to survive as research institutions.
The American research university : an introduction / Roger G. Noll -- Universities, constituencies, and the role of the states / Linda R. Cohen and Roger G. Noll -- Students and research universities / Gary Burtless and Roger G. Noll -- The outlook for federal support of university research / Albert H. Teich -- The economics of university indirect cost reimbursement in federal research grants / Roger G. Noll and William P. Rogerson -- Soft money, hard choices : Research universities and university hospitals / Linda R. Cohen -- Industry and the academy : uneasy partners in the cause of technological advance / Wesley M. Cohen [and others] -- The future of research universities / Roger G. Noll.
Includes bibliographical references and index.
JSTOR
Keywords: Universities and colleges -- United States; Research -- United States; Federal aid to higher education -- United States; Federal aid to research -- United States; Research; Research; United States; Universités -- États-Unis.; Aide de l'État à l'enseignement supérieur -- États-Unis.; Recherche; research (function); Federal aid to higher education; Federal aid to research; Research; Universities and colleges; United States; Finanzierung; Forschung; Universität; USA; EDUCATION / Schools / Levels / Higher